Development of methods of identification and quantitative determination of active substances in semi-solid dosage forms with sapropel extracts - Oksana Strus (Scientific Route OÜ, 2021)
For use in veterinary medicine for the treatment of the wound process and the prevention of mastitis, the composition and technology of an emulsion-based cream, conventionally called “Saprocream”, has been developed. Clinical trial of the drug “Saprocream” proved its effectiveness and safety for use in the healing of microtraumas, erosions and cracks (wounds) of the udders of cows.